MiR-9 and the Midbrain-Hindbrain Boundary: A Showcase for the Limited Functional Conservation and Regulatory Complexity of MicroRNAs - Alwin Prem Anand, A.; Alvarez-Bolado, Gonzalo; Wizenmann, Andrea (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs regulate gene expression at posttranscriptional levels. Some of them appear to regulate brain development and are involved in neurodevelopmental disorders. This has led to the suggestion that the role of microRNAs in neuronal de-velopment and function may be more central than previously appreciated. Here, we review the data about miR-9 function to depict how complex and subtle the functional conservation of this essential developmental regulatory system. On this basis, we propose that species-specific actions of miR-9 could underlie to a large degree spe-cies differences in brain size, shape and function.